If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9 + -1(2n + -6) = 5 + -3n Reorder the terms: 9 + -1(-6 + 2n) = 5 + -3n 9 + (-6 * -1 + 2n * -1) = 5 + -3n 9 + (6 + -2n) = 5 + -3n Combine like terms: 9 + 6 = 15 15 + -2n = 5 + -3n Solving 15 + -2n = 5 + -3n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '3n' to each side of the equation. 15 + -2n + 3n = 5 + -3n + 3n Combine like terms: -2n + 3n = 1n 15 + 1n = 5 + -3n + 3n Combine like terms: -3n + 3n = 0 15 + 1n = 5 + 0 15 + 1n = 5 Add '-15' to each side of the equation. 15 + -15 + 1n = 5 + -15 Combine like terms: 15 + -15 = 0 0 + 1n = 5 + -15 1n = 5 + -15 Combine like terms: 5 + -15 = -10 1n = -10 Divide each side by '1'. n = -10 Simplifying n = -10
| -7-3=8x+4-7x | | 1.4y=4.62 | | 9x+8-8x=13 | | X(2x+3)=(2x+5)(x-1) | | (x/50)=-11+25 | | x+12527=215+12527 | | 2+2.99999999999999999+0.1=n | | 6/5x^2+7x-70=0 | | -14+10=m-3 | | x-12527=215-12527 | | 2a+6=5a-30 | | 16(2x-1)=4(8x+9) | | 40-x=72 | | 2.561x=-12.36963 | | 2[7-5(1-n)]+5n=-6+2[6(n+1)-3n] | | 4y+y=6y-4y | | -(5x-3)-(4x-7)+6=-7(x-4)-(9x+5)+8 | | 8b+20=9b-6 | | 2x^3=384 | | (-3/-4) | | 4(x+5)=2(2x+1)+18 | | 1/4*(x+3)=4x-2(x-3) | | 13-(2f+2)=2(f-2)+3f | | 7(-4+6x)= | | 5x+17y=-13 | | -2+7=15 | | 49x^2+36y^2=1 | | 7x-2(x-2)=5(x+1)+4 | | 6x+8/15x+20 | | 6(2x-5)=2(6x+1) | | 3(x+5)=2(x-6)+x | | 3n+4=6n-3n-8 |